Post-Nearwork Myopic Shift between NonPresbyopia and Presbyopia / Nurul Naquiah Sulaiman - Sulaiman, Nurul Naquiah (2015)
The purpose of the current study was to determine and compare the post-nearwork myopic shift between non-presbyopia and presbyopia. Post-nearwork myopic shift refers to the small, transient, pseudomyopic shift in the far point of the eye after a period of sustained near work. Post-nearwork myopic shift was also defined as shortterm myopic far point shift immediately following a sustained near visual task. The previous studies had been done regarding the comparison between post-nearwork myopic shift in refractive errors and visual discomfort but less was done among early and late presbyopia population (>35 year old). This was a study in determining the initial magnitude of post-nearwork myopic shift between non-presbyopia and presbyopia and to assess the different of initial magnitude of post-nearwork myopic shift between these two groups. This research was conducted in UiTM Puncak Alam, Selangor involving 14 non-presbyopes with no addition power and 9 presbyopes whom at least need +1.00 DS in either eye for near vision in addition to their best corrected distance correction. To allow for dissipation of any residual accommodative transients, subjects remained seated in total darkness for 5 min. After dark adaptation, subjects viewed binocularly at distant target (6 m) for 2 min and immediately focus at near task which was done using the spot-the-difference target for about 5 min with additional lens (if needed). The distant target (6 m) was introduced after the near viewing for about 2 min upon removal of addition lens (if any). Post-nearwork myopic shift was calculated as the difference in five measurements of post-near task distance refractive state compared with the five measurements of pre-near task distance refractive state. The post-nearwork myopic shift initial (mean ± SD) analysed by the Mann-Whitney U test was -0.67 ± 0.61 DS (mean rank = 16.72) for non-presbyopes and -0.15 ± 0.09 DS (mean rank = 8.96) for presbyopes by statistically significantly difference of p = 0.005. At the end of this study, it can be concluded that there was initial magnitude of post-nearwork myopic shift present in all individuals and it was higher in non-presbyope group compared to the presbyope group.